Dampak Pandemi Covid-19 terhadap Implementasi Penyelenggaraan Pelelangan Ikan di TPI Karangsong Indramayu: IMPACT OF THE COVID-19 PANDEMIC - Winda Rianti; Mohamad Sam'un (Program Studi Agribisnis, Fakultas Pertanian, Universitas Singaperbangsa Karawang, 2021)
ABSTRACT The Karangsong Fish Auction Place (FAP) in Indramayu has strategic value for the development of capture fisheries and the economy of the Indramayu community. The Covid-19 pandemic has a negative impact on the achievement of fish production being auctioned at FAP Karangsong, fishermen's income and FAP retribution. The research objective is to determine the impact of the Covid-19 pandemic on the auction of fish production at FAP and what strategies need to be done so that the negative impacts can be minimized. It is a qualitative research supported by quantitative data with a case study approach. Data obtained by in-depth interviews, participant observation, review of documentation and focus group discussions. The data used includes fish production, fish prices and FAP fees compared to the previous year's achievements. Policy implementation is studied with the Van Meter and Van Horn policy implementation model theory. Strategy formulation is carried out by means of a SWOT analysis The results showed that the Covid-19 pandemic had a negative impact on fish auctions at Karangsong FAP. The realization of fish production auctions at FAP in 2019 was 23,654,130 kg, while the realization in 2020 was 18,445,383 kg. The selling price of fish has fallen to 60% from the normal price. Fish marketing and payments have stalled. The realization of FAP charges decreased from 2019 amounting to Rp. 12,076,893,411,- to be in 2020 amounting to Rp. 8,220,770,533,-. The strategies that need to be carried out by the managers of Karangsong FAP in dealing with the Covid-19 pandemic include: 1) Implementing an adaptation strategy, 2) Improving the quality of organizational human resources, 3) Building a network system, 4) Increasing diversification of quality products with high competitiveness, 5) Bringing investors, strengthen business capital and open market breakthroughs, 6) Wise Management of Local Cultural Wisdom. Keywords: adaptation strategy, network system, production.